Design Thinking in Minimum Competency Assessment: Its Effect on Vocational Students’ Numeracy Skills - Sulistiyorini Sulistiyorini; Ida Dwijayanti; Muhtarom Muhtarom (Universitas Islam Sultan Agung, 2025)
Abstract. The 21st century requires individuals to have the ability to think comprehensively, especially in critical and creative thinking. However, there is a significant gap between global competency demands and student competency achievement in Indonesia. The results of the PISA study show that the literacy skills of Indonesian students are still relatively low, including in terms of numeracy or contextual problem solving. Based on a preliminary study of 658 vocational school students in Semarang, as many as 81.9% considered mathematics as a difficult subject. This research uses a qualitative approach with the Design Thinking method and ADDIE R&D model development design. The stages of Design Thinking applied include: the empathize stage to explore students' learning needs through interviews and observations; the definition stage to identify the main problems in learning; the ideate stage to design an AKM-based learning solution; prototype stage to create interactive media and LKPD; as well as the test stage to implement the media and assess its effectiveness through the Minimum Competency Assessment (AKM). Numeracy ability is studied through three main indicators, namely (1) the use of numerical and symbolic representations, (2) information analysis in the form of tables, graphs, images, and diagrams, and (3) the formulation of conclusions or predictions from available data. Data is collected through tests and analyzed descriptively as well as statistical tests. The results of the analysis showed that of 36 students in grade XI of SMK Negeri 1 Semarang, 86% had numeracy skills in the very high category and 14% in the high category, obtained a significance value (Sig.) for class XI TO 2 of 0.109 and for class XI TO 3 of 0.134. Both values are greater than 0.05, so it can be concluded that the data from both classes come from a normally distributed population. The average post-test score of the experimental class was 85.39 higher than the control class of 84.16. This indicates that the work on AKM questions and the use of media based on the Design Thinking approach contribute statistically significantly to improving students' numeracy skills. Thus, AKM has proven to be effective as a measuring tool as well as a strategy to increase numeracy in mathematics learning at vocational schools.Keywords: Minimum Competency Assessment, Numeracy Ability of Vocational School Students, Design Thinking Approach in Mathematics.